2014
DOI: 10.1063/1.4898903
|View full text |Cite
|
Sign up to set email alerts
|

Wear resistance of steels under conditions of dry sliding friction and electric current of high density

Abstract: Abstract. The dependence of current density on the conductivity and the wear rate for the electric contact steel/steel 45 under conditions of dry sliding friction at current density higher 100 А/cm 2 has been presented. It has been determined that the increase in the content of alloying elements or reinforcing phase in the initial structure of the steel leads to lower strength of the surface layer, resulting in a high wear rate of contact and catastrophic wear at a low current density. It has been noted that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 3 publications
(3 reference statements)
0
1
0
Order By: Relevance
“…Moreover, these data could help identify the relationship between the surface layer strength and the initial structure, which would make it possible to more reasonably select the contact pair for extreme friction conditions. The studies performed to this end have demonstrated that a material exhibits high wear resistance in the case where its primary structure contains the least number of phases and chemical elements, when it is pore-free, has no other structure defects, and possesses good plasticity [2,3]. These initial-structure parameters are most evidently observed in steels and in copper.…”
Section: Introductionmentioning
confidence: 93%
“…Moreover, these data could help identify the relationship between the surface layer strength and the initial structure, which would make it possible to more reasonably select the contact pair for extreme friction conditions. The studies performed to this end have demonstrated that a material exhibits high wear resistance in the case where its primary structure contains the least number of phases and chemical elements, when it is pore-free, has no other structure defects, and possesses good plasticity [2,3]. These initial-structure parameters are most evidently observed in steels and in copper.…”
Section: Introductionmentioning
confidence: 93%